The effects of mannan-oligosaccharide supplementation on the skin and gut epithelium health status of European seabass (Dicentrarchus labrax) - Custódio, Marco Freire (2014)
In the present study we assessed the immune-modulatory response of the anterior and posterior gut epithelium and skin of European sea bass when fed two different commercial diets with soybean meal that differ exclusively in the oil type – fish oil and soybean oil - and the effects of their supplementation with MOS. Fish were fed non-supplemented and supplemented diets with 4 g.kg-1 MOS for 8 weeks. All diets resulted in similar weight gains. Microscopic analysis of the anterior gut revealed that the soybean-oil diet with MOS displayed increased (P<0.05) mucous cell area and density compared with its control and the fish-oil based diet with MOS. In the posterior gut no effects on cell density and area were detected in fish fed MOS relative to the controls, however there was an oil-type dependent effect, where fish fed fish-oil based diets had bigger cells (P<0.05) then fish fed soybean-oil based diets. In the skin, no differences on mucous cells parameters were observed between diets. The mucous cells from the skin are larger (P<0.01) than gut’s, and within the gut, the fish fed soybean-oil diets presented bigger (P<0.05) cells in the anterior gut compared with the posterior region. Comparing cell densities, the anterior gut has a higher (P<0.01) density than the posterior gut and the skin, regardless the diet. MOS appears to modulate the innate immunity in the anterior gut. When the diet was soybean-oil based, MOS resulted on a greater storage capacity and density of the mucous cells. A potential effect is also suggested when added to the fish oil diets, with a possibly different mechanism of modulation. This study shows that modulation of mucosal tissues is key to improve resistance against pathogens and that diet composition and prebiotics supplementation are fundamental in the ability of the tissue to exhibit that response.